The Role of Islamic Law in the Formation and Interpretation of Positive Law: A Case Study of the Constitutional Court - Rahmatullah; M. Fijar Ishlahul Ummah; Zezen Zainul Ali (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2025)
This research discusses the role of Islamic law in the formation and interpretation of positive law in Indonesia through a study of the decisions of the Constitutional Court (MK). The main issue raised is the extent to which the principles of Islamic law are accommodated in the national legal system, especially in the process of legislation and judicial review. In a plural legal system like Indonesia, the existence of Islamic law is often faced with the challenge of harmonization with the constitution and the principles of human rights. Therefore, this study aims to examine how the values of Islamic law, such as justice, benefit, and protection of rights, are applied in the jurisprudence of the Constitutional Court and how the normative mechanism of absorption of these values into positive law. The research method used is normative qualitative with a juridical-constitutional approach and analysis of relevant Constitutional Court decisions. Data were obtained from literature studies, documentation of the Constitutional Court's decisions, as well as fiqh literature and Islamic legal theory. The analysis was conducted on sharia principles reflected in the Constitutional Court's decision, including aspects of maqāṣid al-syarī'ah. The results show that the Constitutional Court has selectively integrated Islamic legal values in various decisions, especially those concerning public morals, civil rights, and the Islamic economic system. Although Islamic law is not a formal source of national law, its values have substantially contributed to the formation of positive law and strengthened the ethical and justice dimensions of the Indonesian legal system.